Attributes of Effective Lecturing in the College Classroom - Schonwetter, Dieter J. (Canadian Journal of Higher Education, 1993)
The following paper highlights research on effective lecturing in the college classroom. First, critical issues concerning the operational definition of effective lecturing and the measurement criteria used to denote it are addressed. Next, major research findings are reported, beginning with correlational information reported by descriptive studies and ending with causal findings demonstrated by empirical studies. Current research literature identifies the following lecture attributes as important for student learning: expressiveness, clarity, and organization. These dimensions are defined by low-inference behaviours and supported by empirical studies. Furthermore, links between lecture attributes and certain student cognitive processing activities, explaining the facilitative qualities of effective lecturing on student learning, are hypothesized. Finally, implications for both practitioners and researchers are discussed.